Composite solid electrolyte membrane and preparation method and application thereof
By forming an electrolyte gel layer on the surface of the organic polymer three-dimensional fiber web, the problems of low conductivity and poor consistency of solid electrolyte materials are solved, and high ionic conductivity and good mechanical properties are achieved.
Patent Information
- Application Number
- CN202411892658.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
The existing solid-state electrolyte materials have problems such as low conductivity, complex manufacturing process and poor consistency, which limits their application in solid-state batteries.
An organic polymer three-dimensional fiber web is used as a self-supporting structural layer, and an electrolyte-like gel layer is formed in situ on its surface. A hydroxyl-containing solvent reacts with an inorganic salt electrolyte to form a stable gel-like layer to improve ion conduction ability.
By creating long-range continuous ion conduction channels and large porosity structures, the ionic conductivity of the composite solid electrolyte membrane is significantly improved, solving the problems of low conductivity and poor consistency, while maintaining strength and flexibility.
Smart Images

Figure CN119674211A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid electrolyte materials and relates to a composite solid electrolyte membrane and a preparation method and application thereof. Background Art
[0002] Solid-state batteries can essentially solve the technical problems of low safety and limited energy density of existing liquid metal batteries. Solid electrolytes, as core components, are mainly divided into organic polymer electrolytes, inorganic electrolytes and organic / inorganic composite solid electrolytes. Among them, inorganic electrolytes have low ionic conductivity, large interface impedance between particles, large interface impedance with electrodes, brittle electrolyte sheets, and cannot inhibit the growth of metal dendrites, which have serious safety problems after long-term circulation; organic polymer electrolytes have significant advantages, such as versatility, flexibility and lightness of shape, making it easier to form a good electrode / electrolyte contact surface, but their inherent low room temperature ionic conductivity seriously hinders the practical application of organic polymer electrolytes; organic / inorganic composite solid electrolytes combine the advantages of the above two electrolytes, and can be mass-produced, which also reduces the manufacturing cost of solid-state batteries, but these three solid electrolytes still generally have problems such as low conductivity, complex manufacturing process and poor consistency, which restricts their further application in solid-state batteries.
[0003] CN110224174A discloses a metal organic framework composite comb polymer, which combines the fast ion transmission characteristics of the comb polymer branched structure with the nanopore adsorption effect of the metal organic framework to obtain a composite organic solid electrolyte battery with an ion conductivity of 9.9×10 -5 Scm -1 , the ionic conductivity is still low; a higher content of inorganic phase is required in the composite solid electrolyte to achieve ion percolation brought about by the interconnection of the inorganic phase. In this case, there are problems of side reactions at the interface of inorganic particles and the resulting conductivity attenuation.
[0004] CN112563562A discloses adding a polymer substrate and a lithium salt into anhydrous acetonitrile to form a solution, and then coating the solution on an LLZO solid electrolyte sheet to improve the contact performance between the solid electrolyte and the electrode. The composite solid electrolyte uses inorganic phase percolation as the main ion-conducting channel, and the interface between the inorganic phase and the electrode sheet is mainly hard contact. The interface contact is prone to failure and usually requires a transition layer.
[0005] Therefore, in this field, there is an urgent need to develop a composite solid electrolyte to solve the above problems. Summary of the invention
[0006] The purpose of the present invention is to provide a composite solid electrolyte membrane and a preparation method and application thereof. In the composite solid electrolyte membrane of the present invention, the organic polymer three-dimensional fiber network serves as a powerful interconnected framework, has a high specific surface area and a fully interconnected open porous structure, and can create a long-range continuous ion conduction channel in the composite solid electrolyte membrane, thereby enhancing ion conduction. An inorganic salt electrolyte solution containing a hydroxyl solvent is used to react with the organic polymer three-dimensional fiber network to form an electrolyte gel layer in situ on the surface of the organic polymer three-dimensional fiber network, which can achieve rapid transmission of ions at the two-phase interface.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a composite solid electrolyte membrane, the composite solid electrolyte membrane comprising an organic polymer three-dimensional fiber network and an electrolyte gel layer coated on the surface of the organic polymer three-dimensional fiber network;
[0009] The electrolyte gel layer includes an inorganic salt electrolyte and a hydroxyl-containing solvent.
[0010] The composite solid electrolyte membrane of the present invention adopts an organic polymer three-dimensional fiber mesh as a self-supporting structural layer. The organic polymer three-dimensional fiber mesh has the advantages of high surface area and strong interconnected framework, and can create a long-range continuous ion conduction channel in the matrix to enhance ion conduction. The surface of the organic polymer three-dimensional fiber mesh is coated with an electrolyte gel layer. The special structure enables the composite solid electrolyte membrane to achieve large porosity and connectivity between pores. The fully interconnected open porous structure provides a good ion conduction channel and a large specific surface area. The gel-like layer of the present invention adopts a hydroxyl-containing solvent, and the selected polymer fiber will not be dissolved or swollen by a pure hydroxyl solvent. However, after adding salt in a specific concentration range, the mixture of salt and solvent can form coordination bonds and hydrogen bonds with the polar groups of the polymer molecules, enter the polymer to reduce the cohesion between the polymer molecular chains, and realize the dissolution or swelling of the polymer. Because the interaction between salt, solvent, and polymer molecules can only be realized within a specific concentration range, the combination of two components alone cannot form a gel-like structure, so the skin-core structure formed by the three is more stable. The gel-like layer ensures the rapid transport of ions and avoids the high liquid absorption of the gel electrolyte, and the inner core structure also ensures the strength of the solid electrolyte.
[0011] Preferably, the material of the organic polymer three-dimensional fiber mesh includes any one of polyacrylonitrile, polyvinyl chloride, polyvinylidene fluoride, polymethyl methacrylate, polyimide, polystyrene or chitosan, or a combination of at least two of them. Typical but non-limiting combinations include a combination of polyacrylonitrile and polyvinyl chloride, a combination of polyvinyl chloride and polyvinylidene fluoride, or a combination of polyacrylonitrile and chitosan, etc.
[0012] Preferably, inorganic particles are also arranged on the surface and / or in the gaps of the organic polymer three-dimensional fiber web.
[0013] The present invention adds inorganic matter to the surface and / or gaps of the organic polymer three-dimensional fiber web. The inorganic matter can improve the structural stability of the organic polymer three-dimensional fiber web and its supporting performance, while making the organic polymer three-dimensional fiber web have a higher shell layer ratio and avoiding the merging of adjacent fiber shell layers.
[0014] Preferably, the inorganic particles include any one of zirconium oxide, tin oxide, aluminum oxide, yttrium oxide, bismuth oxide, zinc oxide, titanium oxide, silicon oxide or boron nitride, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of zirconium oxide and tin oxide, a combination of zirconium oxide and yttrium oxide, or a combination of aluminum oxide and bismuth oxide, etc.
[0015] Preferably, the mass ratio of the organic polymer three-dimensional fiber web to the inorganic particles is 1:(1-4), for example: 1:1, 1:1.5, 1:2, 1:3 or 1:4, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] The present invention regulates the mass ratio of the organic polymer three-dimensional fiber web to the inorganic particles so that a three-dimensional continuous ion transmission channel is formed at the interface between the organic polymer three-dimensional fiber web and the inorganic particles. If the content of the inorganic particles is too high, the three-dimensional channel will be reduced and the ion conductivity will decrease. Otherwise, the strength will decrease and the flexibility and processability will be lost.
[0017] Preferably, the inorganic salt electrolyte includes any one of lithium salt, sodium salt, potassium salt, magnesium salt, zinc salt, aluminum salt, iron salt, nickel salt, cobalt salt or manganese salt, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of lithium salt and sodium salt, a combination of sodium salt and potassium salt, or a combination of magnesium salt and zinc salt, etc.
[0018] Preferably, the lithium salt includes any one of lithium thiocyanate, lithium perchlorate, lithium iodide, lithium bromide, lithium chloride, lithium nitrate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate or lithium bis(oxalatoborate), or a combination of at least two thereof. Typical but non-limiting combinations include a combination of lithium perchlorate and lithium bromide, a combination of lithium perchlorate and lithium chloride, or a combination of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide, etc.
[0019] Preferably, the sodium salt includes any one of sodium thiocyanate, sodium perchlorate, sodium iodide, sodium sulfide, sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, sodium difluorooxalate borate or sodium trifluoromethanesulfonate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of sodium perchlorate and sodium iodide, a combination of sodium bis(trifluoromethylsulfonyl)imide and sodium difluorooxalate borate, or a combination of sodium difluorooxalate borate and sodium trifluoromethanesulfonate, etc.
[0020] Preferably, the potassium salt comprises any one of potassium thiocyanate, potassium perchlorate, potassium bis(fluorosulfonyl)imide, potassium bis(trifluoromethylsulfonyl)imide or potassium hexafluorophosphate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of potassium perchlorate and potassium iodide, a combination of potassium bis(trifluoromethylsulfonyl)imide and potassium difluorooxalate borate, or a combination of potassium difluorooxalate borate and potassium trifluoromethanesulfonate, etc.
[0021] Preferably, the magnesium salt comprises any one of magnesium thiocyanate, magnesium perchlorate, magnesium iodide, magnesium bromide, magnesium chloride, magnesium bis(trifluoromethylsulfonyl)imide or magnesium trifluoromethanesulfonate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of magnesium iodide and magnesium bromide, a combination of magnesium iodide and magnesium chloride, or a combination of magnesium bis(trifluoromethylsulfonyl)imide and magnesium trifluoromethanesulfonate, etc.
[0022] Preferably, the zinc salt comprises any one of zinc thiocyanate, zinc perchlorate, zinc iodide, zinc bromide, magnesium chloride, zinc trifluoromethanesulfonate or zinc bis[bis(trifluoromethylsulfonyl)imide], or a combination of at least two thereof. Typical but non-limiting combinations include a combination of zinc perchlorate and zinc iodide, a combination of zinc bromide and zinc chloride, or a combination of zinc trifluoromethanesulfonate and zinc bis[bis(trifluoromethylsulfonyl)imide], and the like.
[0023] Preferably, the aluminum salt includes any one of aluminum thiocyanate, aluminum perchlorate, aluminum iodide, aluminum bromide, aluminum chloride or aluminum nitrate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of aluminum iodide and aluminum bromide, a combination of aluminum bromide and aluminum chloride, or a combination of aluminum thiocyanate and aluminum perchlorate, etc.
[0024] Preferably, the iron salt includes any one of ferric thiocyanate, ferric perchlorate, ferric iodide, ferric bromide, ferric chloride or ferric nitrate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of ferric thiocyanate and ferric perchlorate, a combination of ferric iodide and ferric bromide, or a combination of ferric chloride and ferric nitrate.
[0025] Preferably, the nickel salt includes any one of nickel thiocyanate, nickel perchlorate, nickel iodide or nickel bromide, or a combination of at least two of them. Typical but non-limiting combinations include a combination of nickel iodide and nickel bromide, a combination of nickel perchlorate and nickel iodide, or a combination of nickel thiocyanate and nickel perchlorate, etc.
[0026] Preferably, the cobalt salt includes any one of cobalt thiocyanate, cobalt perchlorate, cobalt iodide, cobalt bromide or cobalt nitrate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of cobalt thiocyanate and cobalt perchlorate, a combination of cobalt iodide and cobalt bromide, or a combination of cobalt bromide and cobalt nitrate, etc.
[0027] Preferably, the manganese salt includes any one of manganese thiocyanate, manganese perchlorate or manganese nitrate, or a combination of at least two of them. Typical but non-limiting combinations include a combination of manganese thiocyanate and manganese perchlorate, a combination of manganese perchlorate and manganese nitrate, or a combination of manganese thiocyanate and manganese nitrate.
[0028] Preferably, the hydroxyl-containing solvent comprises water and / or an alcohol solvent.
[0029] Preferably, the alcohol solvent includes any one of methanol, ethanol, propanol, isopropanol, butanol, isobutanol, tert-butanol, ethylene glycol, propylene glycol, butylene glycol, diethylene glycol, triethylene glycol or tetraethylene glycol, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of methanol and ethanol, a combination of ethanol and ethylene glycol, or a combination of propylene glycol and butylene glycol.
[0030] Preferably, in the electrolyte gel layer, the molar concentration of the inorganic salt electrolyte is 2.5 mol / L to 12 mol / L, for example: 2.5 mol / L, 4.5 mol / L, 6.5 mol / L, 9.5 mol / L, 12 mol / L, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 4.5 mol / L to 9.5 mol / L.
[0031] Preferably, the mass ratio of the organic polymer three-dimensional fiber network and the electrolyte gel layer is (0.8-20):1, for example: 0.8:1, 1:1, 5:1, 10:1, 15:1 or 20:1, etc., not limited to the listed values, other unlisted values within the numerical range are also applicable, preferably (3-8):1.
[0032] The present invention adjusts the mass ratio of the organic polymer three-dimensional fiber web to the electrolyte gel layer so that the organic polymer three-dimensional fiber web can ensure the transmission of ions while having sufficient strength to ensure the normal use of the solid electrolyte membrane. If the mass ratio of the electrolyte gel layer is too low, the ion conductivity will be low, otherwise it will lose its strength as a solid electrolyte membrane.
[0033] In a second aspect, the present invention provides a method for preparing the composite solid electrolyte membrane as described in the first aspect, the preparation method comprising the following steps:
[0034] (1) spraying an organic polymer solution onto a receiving surface by electrospinning to form a polymer three-dimensional fiber web;
[0035] (2) Mixing an inorganic salt electrolyte solution with a polymer three-dimensional fiber network, and drying the mixture to obtain the composite solid electrolyte membrane.
[0036] The present invention uses electrostatic spinning technology to form a fibrous organic polymer primary structure from an organic polymer solution. On the receiving surface of the spray, the primary structure in the form of fibers aggregates to form a polymer three-dimensional fiber network with a three-dimensional secondary structure, which is then mixed with an inorganic salt electrolyte solution. After the two are in contact, since the salt solution contains a hydroxyl-containing solvent, the hydroxyl-containing solvent reacts with the polymer three-dimensional fiber network to form a gel-like layer on its surface. The gel-like layer can assist the dissociation and transportation of electrolyte salt ions, and since the polymer three-dimensional fiber network is three-dimensionally connected, the electrolyte salt ions can migrate quickly, thereby achieving high ionic conductivity.
[0037] Preferably, the solvent of the organic polymer solution in step (1) comprises any one of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone, or a combination of at least two thereof.
[0038] Preferably, the concentration of the organic polymer solution in step (1) is 5% to 20%, for example, 5%, 8%, 10%, 15% or 20%, etc., and is not limited to the listed values. Other values not listed within the range are also applicable.
[0039] Preferably, the voltage of the electrospinning in step (1) is 10 kV to 30 kV, for example, 10 kV, 12 kV, 20 kV, 25 kV or 30 kV, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0040] Preferably, the liquid flow rate of the electrospinning in step (1) is 5 μL / min to 50 μL / min, for example, 5 μL / min, 10 μL / min, 20 μL / min, 30 μL / min or 50 μL / min, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, after the electrospinning treatment in step (1), the obtained polymer three-dimensional fiber web is subjected to a pressing treatment.
[0042] Preferably, the pressure of the pressing treatment is 10 MPa to 80 MPa, for example, 10 MPa, 20 MPa, 50 MPa, 60 MPa, 70 MPa or 80 MPa, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] Preferably, during the electrospinning in step (1), the inorganic particle dispersion is sprayed onto a receiving surface by electrostatic spraying to mix with the polymer three-dimensional fiber web.
[0044] Preferably, the solvent of the inorganic particle dispersion includes any one of water, ethanol, isopropanol or N,N-dimethylformamide, or a combination of at least two thereof.
[0045] Preferably, the mass concentration of the inorganic particle dispersion is 2% to 20%, for example, 2%, 5%, 8%, 10%, 15% or 20%.
[0046] Preferably, the liquid flow rate of the electrostatic spray is 20 μL / min to 80 μL / min, for example, 50 μL / min, 55 μL / min, 60 μL / min, 70 μL / min or 80 μL / min, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] Preferably, the voltage of the electrostatic spray is 10 kV to 30 kV, for example, 10 kV, 12 kV, 15 kV, 18 kV or 20 kV, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0048] Preferably, the spraying distances of the electrospinning and electrostatic spraying are independently 3 cm to 25 cm, for example, 3 cm, 5 cm, 8 cm, 10 cm or 25 cm, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0049] Preferably, the molar concentration of the inorganic salt electrolyte solution in step (2) is 2.5 mol / L to 12 mol / L, for example: 2.5 mol / L, 4.5 mol / L, 6.5 mol / L, 9.5 mol / L, 12 mol / L, etc., not limited to the listed values, other unlisted values within the numerical range are also applicable, preferably 4.5 mol / L to 9.5 mol / L.
[0050] Preferably, the mixing method in step (2) includes dipping and / or spraying.
[0051] Preferably, the drying in step (2) comprises vacuum drying.
[0052] Preferably, the drying temperature in step (2) is 60°C to 80°C, for example, 60°C, 65°C, 70°C, 75°C or 80°C, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0053] The present invention performs drying at low temperature, the solvent in the gel layer is not easy to volatilize, the salt and the solvent participate in the formation of the gel-like layer together, and there is no weight loss.
[0054] In a third aspect, the present invention provides a secondary battery, wherein the secondary battery comprises the composite solid electrolyte membrane as described in the first aspect.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] (1) In the composite solid electrolyte membrane of the present invention, the organic polymer three-dimensional fiber network serves as a strong interconnected framework, has a high specific surface area and a fully interconnected open porous structure, and can create a long-range continuous ion conduction channel in the composite solid electrolyte membrane, thereby enhancing ion conduction. An inorganic salt electrolyte solution containing a hydroxyl solvent is used to react with the organic polymer three-dimensional fiber network to form an electrolyte gel layer in situ on the surface of the organic polymer three-dimensional fiber network, which can achieve rapid transmission of ions at the interface between the two phases.
[0057] (2) The hydroxyl-containing solvent of the present invention reacts with the polymer three-dimensional fiber network to form a special gel-like structure on the surface of the polymer filaments, which is beneficial to the transmission of salt ions, thereby improving ionic conductivity. The polymer three-dimensional fiber network is three-dimensionally interconnected, and each individual filament structure has a self-supporting structure in the middle, and the outer layer is a solvent interaction layer of a gel-like salt solution, which has fast salt ion transmission and low interface impedance, and is beneficial to the capacity and rate of the secondary battery.
[0058] (3) The lithium ion conductivity of the composite solid electrolyte membrane of the present invention can reach 1.22×10 -4 S / cm, and by adjusting the preparation conditions and feed ratio, the lithium ion conductivity of the composite solid electrolyte membrane can reach 2.54×10 -3 S / cm. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is a schematic cross-sectional view of a single fiber in the composite solid electrolyte membrane described in Example 1 of the present invention, wherein 1 is the polyacrylonitrile fiber core, and 2 is the electrolyte gel layer.
[0060] Figure 2 This is an electrochemical window test diagram of the composite solid electrolyte membrane described in Example 3 of the present invention. DETAILED DESCRIPTION
[0061] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0062] The embodiment of the present invention uses the device described in Example 2 of CN208336405U to perform electrostatic spinning and electrostatic spraying.
[0063] Example 1
[0064] This embodiment provides a composite solid electrolyte membrane, the composite solid electrolyte membrane comprising a polyacrylonitrile three-dimensional fiber web, zirconium oxide particles attached to the gaps and surface of the polyacrylonitrile three-dimensional fiber web, and the surface of the polyacrylonitrile three-dimensional fiber web (including zirconium oxide particles) is coated with an electrolyte gel layer;
[0065] The electrolyte gel layer includes lithium perchlorate (electrolyte) and ethylene glycol (solvent);
[0066] The mass ratio of the polyacrylonitrile three-dimensional fiber web to the zirconium oxide particles is 1:2, and the mass ratio of the polyacrylonitrile three-dimensional fiber web to the electrolyte gel layer is 10:1.
[0067] In the composite solid electrolyte membrane, the structural schematic diagram of a single fiber is as follows: Figure 1 As shown:
[0068] Depend on Figure 1 It can be seen that in the composite solid electrolyte membrane, a single fiber filament is composed of a polyacrylonitrile fiber core 1 and an electrolyte gel layer 2 coated on the surface of the polyacrylonitrile fiber core 1 (since the inorganic particles are not evenly distributed on the fiber filament, not all positions on the fiber filament contain inorganic particles, so they are not shown in the cross-sectional view).
[0069] The composite solid electrolyte membrane is prepared by the following method:
[0070] The electrostatic spinning technology is used to spray a polyacrylonitrile solution with a mass concentration of 10% onto a selected receiving surface and the polyacrylonitrile fibers are aggregated or stacked to form an organic secondary structure. At the same time as the electrostatic spinning, a zirconium oxide particle dispersion with a mass concentration of 5% is sprayed onto the selected receiving surface by electrostatic spraying to obtain a composite material composed of the organic secondary structure and zirconium oxide particles, wherein spinning and spraying are carried out simultaneously in a shoulder-to-shoulder parallel form at a voltage of 15kV, the distance between the two nozzles and the roller receiving device is 6cm, the flow rate of the polyacrylonitrile solution in the spinning nozzle is 10μL / min, and the flow rate of the zirconium oxide particle dispersion in the spray nozzle is about 50μL / min. After working for 3 hours, a flexible film can be peeled off from the roller receiving device, and then rolled at 50MPa to obtain a polymer three-dimensional fiber network;
[0071] 0.03 g of ethylene glycol solution of lithium perchlorate with a mass concentration of 2.5 mol / L was sprayed onto the surface of the polymer three-dimensional fiber network, and the composite solid electrolyte membrane was obtained after vacuuming and baking at 70° C.
[0072] Example 2
[0073] This embodiment provides a composite solid electrolyte membrane, the composite solid electrolyte membrane comprising a polystyrene three-dimensional fiber mesh, zirconium oxide particles attached to the gaps and surface of the polystyrene three-dimensional fiber mesh, and the surface of the polystyrene three-dimensional fiber mesh (including the zirconium oxide particles) is coated with an electrolyte gel layer;
[0074] The electrolyte gel layer includes lithium perchlorate (electrolyte) and ethylene glycol (solvent);
[0075] The mass ratio of the polystyrene three-dimensional fiber mesh to the zirconium oxide particles is 1:2, and the mass ratio of the polystyrene three-dimensional fiber mesh to the electrolyte gel layer is 8:1.
[0076] The composite solid electrolyte membrane is prepared by the following method:
[0077] The electrostatic spinning technology is used to spray a polystyrene solution with a mass concentration of 20% onto a selected receiving surface and the polystyrene fibers are aggregated or stacked to form an organic secondary structure. At the same time as the electrostatic spinning, a zirconium oxide particle dispersion with a mass concentration of 5% is sprayed onto the selected receiving surface by electrostatic spraying to obtain a composite material composed of the organic secondary structure and zirconium oxide particles, wherein spinning and spraying are carried out simultaneously in a shoulder-to-shoulder parallel form at a voltage of 10kV, the distance between the two nozzles and the roller receiving device is 3cm, the flow rate of the polystyrene solution in the spinning nozzle is 5μL / min, and the flow rate of the zirconium oxide particle dispersion in the spray nozzle is about 50μL / min. After working for 4 hours, a flexible film can be peeled off from the roller receiving device, and then rolled at 30MPa to obtain a polymer three-dimensional fiber network;
[0078] 0.05 g of ethylene glycol solution of lithium perchlorate with a mass concentration of 4.5 mol / L was sprayed onto the surface of the polymer three-dimensional fiber network, and the composite solid electrolyte membrane was obtained after vacuuming and baking at 70° C.
[0079] Example 3
[0080] The present embodiment provides a composite solid electrolyte membrane, the composite solid electrolyte membrane comprising a polyvinylidene fluoride three-dimensional fiber web, zirconium oxide particles attached to the gaps and surface of the polyvinylidene fluoride three-dimensional fiber web, and the surface of the polyvinylidene fluoride three-dimensional fiber web (including the zirconium oxide particles) is coated with an electrolyte gel layer;
[0081] The electrolyte gel layer includes lithium perchlorate (electrolyte) and ethylene glycol (solvent);
[0082] The mass ratio of the three-dimensional polyvinylidene fluoride fiber web to the zirconium oxide particles is 1:2, and the mass ratio of the three-dimensional polyvinylidene fluoride fiber web to the electrolyte gel layer is 3:1.
[0083] The composite solid electrolyte membrane is prepared by the following method:
[0084] The electrostatic spinning technology is used to spray a polyvinylidene fluoride solution with a mass concentration of 15% onto a selected receiving surface and the polyvinylidene fluoride fibers are aggregated or stacked to form an organic secondary structure. At the same time as the electrostatic spinning, a zirconium oxide particle dispersion with a mass concentration of 7% is sprayed onto the selected receiving surface by electrostatic spraying to obtain a composite material composed of the organic secondary structure and zirconium oxide particles, wherein spinning and spraying are carried out simultaneously in a shoulder-to-shoulder parallel form at a voltage of 20kV, the distance between the two nozzles and the roller receiving device is 7cm, the flow rate of the polyvinylidene fluoride solution in the spinning nozzle is 15μL / min, and the flow rate of the zirconium oxide particle dispersion in the spray nozzle is about 80μL / min. After working for 2 hours, a flexible film can be peeled off from the roller receiving device, and then rolled at 50MPa to obtain a polymer three-dimensional fiber web;
[0085] 0.1 g of ethylene glycol solution of lithium perchlorate with a mass concentration of 9.5 mol / L was sprayed onto the surface of the polymer three-dimensional fiber network, and the composite solid electrolyte membrane was obtained after vacuuming and baking at 70° C.
[0086] The electrochemical window test diagram of the composite solid electrolyte membrane is as follows: Figure 2 shown.
[0087] Example 4
[0088] The only difference between this embodiment and embodiment 1 is that the mass concentration of the ethylene glycol solution of lithium perchlorate is 12 mol / L, and the mass ratio of the polyacrylonitrile three-dimensional fiber network to the electrolyte gel layer in the composite solid electrolyte membrane is 2:1. The other embodiments are exactly the same as embodiment 1.
[0089] Example 5
[0090] The only difference between this embodiment and embodiment 1 is that the mass concentration of the ethylene glycol solution of lithium perchlorate is 6.5 mol / L, and the mass ratio of the polyacrylonitrile three-dimensional fiber network to the electrolyte gel layer in the composite solid electrolyte membrane is 5:1. The other embodiments are exactly the same as embodiment 1.
[0091] Example 6
[0092] The only difference between this embodiment and embodiment 5 is that lithium perchlorate is replaced by sodium perchlorate, and other conditions and parameters are exactly the same as those in embodiment 5.
[0093] Example 7
[0094] The only difference between this embodiment and embodiment 5 is that lithium perchlorate is replaced by magnesium perchlorate, and other conditions and parameters are exactly the same as those in embodiment 5.
[0095] Example 8
[0096] The only difference between this embodiment and embodiment 5 is that lithium perchlorate is replaced by zinc chloride, and other conditions and parameters are exactly the same as those in embodiment 5.
[0097] Example 9
[0098] The only difference between this embodiment and embodiment 5 is that lithium perchlorate is replaced by aluminum chloride, and other conditions and parameters are exactly the same as those in embodiment 5.
[0099] Example 10
[0100] The only difference between this embodiment and embodiment 5 is that the ethylene glycol solution of lithium perchlorate is replaced with a triethylene glycol solution of zinc chloride of the same concentration, and the other conditions and parameters are exactly the same as those of embodiment 5.
[0101] Embodiment 11
[0102] The only difference between this embodiment and embodiment 5 is that the ethylene glycol solution of lithium perchlorate is replaced with a tetraethylene glycol solution of zinc chloride of the same concentration, and the other conditions and parameters are exactly the same as those of embodiment 5.
[0103] Example 12
[0104] The only difference between this embodiment and embodiment 5 is that zirconium oxide is not added, and other conditions and parameters are exactly the same as those of embodiment 5.
[0105] Embodiment 13
[0106] The only difference between this embodiment and Embodiment 5 is that the mass ratio of the polyacrylonitrile three-dimensional fiber web to zirconium oxide is 1:0.5, and the other conditions and parameters are exactly the same as those in Embodiment 5.
[0107] Embodiment 14
[0108] The only difference between this embodiment and Embodiment 5 is that the mass ratio of the polyacrylonitrile three-dimensional fiber web to zirconium oxide is 1:5, and the other conditions and parameters are exactly the same as those in Embodiment 5.
[0109] Comparative Example 1
[0110] In this comparative example, zirconium oxide, polyacrylonitrile, lithium perchlorate and ethylene glycol are directly mixed in a mass ratio of 2:1:1:1 to prepare a solid electrolyte membrane.
[0111] Comparative Example 2
[0112] The only difference between this comparative example and Example 5 is that ethylene glycol is replaced with ethylene glycol dimethyl ether, and the other conditions and parameters are exactly the same as those in Example 5.
[0113] Comparative Example 3
[0114] The only difference between this comparative example and Example 5 is that lithium perchlorate is not added, and other conditions and parameters are exactly the same as those in Example 5. After testing, only a polyacrylonitrile three-dimensional fiber web is obtained, and there is no gel layer on the surface.
[0115] Performance Test:
[0116] The composite solid electrolyte membranes prepared in the examples and comparative examples were cut to produce disc-shaped samples with a diameter of 10 to 19 mm and a thickness of 10 μm to 50 μm. The composite solid electrolyte discs were assembled into a "gold-plated copper sheet / electrolyte / gold-plated copper sheet" simulated experimental battery, and the battery was subjected to an external pressure of 10 MPa.
[0117] Open the electrochemical workstation and call the electrochemical impedance spectroscopy (EIS) program. Set the test frequency range to 1MHz~100mHz and the disturbance voltage to 10mV. Perform the test and obtain the corresponding Nyquist spectrum.
[0118] The resistance R is obtained by circuit fitting of the Nyquist spectrum, and the ionic conductivity σ of the composite solid electrolyte is calculated according to the formula.
[0119] σ=L / (R·S);
[0120] S——Cross-sectional area of standard stainless steel gasket, in square centimeters (cm 2 );
[0121] L——thickness of solid electrolyte, in centimeters (cm);
[0122] R is the resistance measurement value of the solid electrolyte, in ohms (Ω). The test results are shown in Table 1:
[0123] Table 1
[0124]
[0125]
[0126] As can be seen from Table 1, according to Examples 1-11, the lithium ion conductivity of the composite solid electrolyte membrane of the present invention can reach 1.22×10 -4 S / cm, and by adjusting the preparation conditions and feed ratio, the lithium ion conductivity of the composite solid electrolyte membrane can reach 2.54×10 -3 S / cm.
[0127] By comparison of Examples 1-5, it can be seen that in the preparation process of the composite solid electrolyte membrane of the present invention, the mass concentration of the inorganic salt electrolyte solution used will affect its performance. When the molar concentration of the inorganic salt electrolyte solution is controlled at 4.5 mol / L to 9.5 mol / L, the performance of the solid electrolyte membrane obtained is better. If the concentration of the inorganic salt electrolyte solution is too low, the salt ions are surrounded by solvent molecules and cannot contact the polymer to form a gel layer. If the concentration of the inorganic salt electrolyte solution is too high, the solvent molecules are bound by the salt and their mobility is significantly reduced, and they cannot completely enter the polymer molecular chains to form a uniform gel layer.
[0128] From the comparison between Example 5 and Examples 6-11, it can be seen that the composite solid electrolyte membrane of the present invention has a wide variety of electrolyte salts and electrolyte salt solutions to choose from, and has good universality.
[0129] By comparing Example 5 and Example 12, it can be seen that the present invention adds inorganic matter to the surface and / or gaps of the organic polymer three-dimensional fiber web. The inorganic matter can improve the structural stability of the organic polymer three-dimensional fiber web, improve its supporting performance, and at the same time make the organic polymer three-dimensional fiber web have a higher shell ratio.
[0130] By comparing Example 5 with Examples 13-14, it can be seen that in the preparation process of the composite solid electrolyte membrane of the present invention, the mass ratio of the organic polymer three-dimensional fiber web to the inorganic particles will affect its performance. When the mass ratio of the organic polymer three-dimensional fiber web to the inorganic particles is controlled at 1:(1-4), the performance of the solid electrolyte membrane obtained is better. If the amount of inorganic particles added is too high, the strength of the composite solid electrolyte membrane decreases, and the flexibility and processability are lost. The cross-connections between polymer fibers are reduced, the three-dimensional channels are reduced, and the ionic conductivity is reduced. If the amount of inorganic particles added is too low, the three-dimensional channels of adjacent filament shell layers are reduced, and the ionic conductivity is reduced.
[0131] By comparing Example 5 with Comparative Example 1, it can be seen that the composite solid electrolyte membrane of the present invention uses an organic polymer three-dimensional fiber mesh as a self-supporting structural layer. The organic polymer three-dimensional fiber mesh has the advantages of high surface area and a strong interconnected framework, and can create a long-range continuous ion conduction channel in the matrix to enhance ion conduction. The surface of the organic polymer three-dimensional fiber mesh is coated with an electrolyte gel layer. The special structure enables the composite solid electrolyte membrane to achieve a large porosity and connectivity between pores. The fully interconnected open porous structure provides a good ion conduction channel and a large specific surface area.
[0132] By comparing Example 5 with Comparative Example 2, it can be seen that the gel-like layer of the present invention uses a hydroxyl-containing solvent, and the selected polymer fiber will not be dissolved or swollen by a pure hydroxyl solvent. However, after adding salt in a specific concentration range, the mixture of salt and solvent can form coordination bonds and hydrogen bonds with the polar groups of the polymer molecules, enter the interior of the polymer to reduce the cohesive force between the polymer molecular chains, and achieve dissolution or swelling of the polymer. Because the interaction between salt, solvent, and polymer molecules can only be achieved within a specific concentration range, the combination of two components alone cannot form a gel-like structure, so the skin-core structure formed by the three is more stable. The salt solution of non-hydroxyl solvent does not have this phenomenon of forming coordination bonds and hydrogen bonds with the polymer at the same time, and cannot form a gel-like layer within the preferred concentration range. The lithium salt and solvent are in an unstable state in the membrane, and salt is easily precipitated, and the ionic conductivity is low.
[0133] From the comparison between Example 5 and Comparative Example 3, it can be seen that the solubility parameters of the hydroxyl solvent and the selected polymer are quite different. In the absence of inorganic salt ions, the hydroxyl solvent cannot dissolve or swell the selected polymer, and thus cannot form a gel-like layer.
[0134] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A composite solid electrolyte membrane, characterized in that: The composite solid electrolyte membrane comprises an organic polymer three-dimensional fiber network and an electrolyte gel layer coated on the surface of the organic polymer three-dimensional fiber network; The electrolyte gel layer includes an inorganic salt electrolyte and a hydroxyl-containing solvent.
2. The composite solid electrolyte membrane according to claim 1, characterized in that The material of the organic polymer three-dimensional fiber network includes polyacrylonitrile, polyvinyl chloride, polyvinylidene fluoride, polymethyl methacrylate, polyimide, polystyrene, chitosan or any one thereof or a combination of at least two thereof.
3. The composite solid electrolyte membrane according to claim 1, characterized in that: Inorganic particles are also arranged on the surface and / or in the gaps of the organic polymer three-dimensional fiber web; Preferably, the inorganic particles include any one or a combination of at least two of zirconium oxide, tin oxide, aluminum oxide, yttrium oxide, bismuth oxide, zinc oxide, titanium oxide, silicon oxide or boron nitride; Preferably, the mass ratio of the organic polymer three-dimensional fiber network to the inorganic particles is 1:(1-4).
4. The composite solid electrolyte membrane according to any one of claims 1 to 3, characterized in that: The inorganic salt electrolyte includes any one of lithium salt, sodium salt, potassium salt, magnesium salt, zinc salt, aluminum salt, iron salt, nickel salt, cobalt salt or manganese salt, or a combination of at least two thereof; Preferably, the lithium salt includes any one of lithium thiocyanate, lithium perchlorate, lithium iodide, lithium bromide, lithium chloride, lithium nitrate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate or lithium bis(oxalatoborate) or a combination of at least two thereof; Preferably, the sodium salt comprises any one of sodium thiocyanate, sodium perchlorate, sodium iodide, sodium sulfide, sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, sodium difluorooxalatoborate or sodium trifluoromethanesulfonate, or a combination of at least two thereof; Preferably, the potassium salt comprises any one of potassium thiocyanate, potassium perchlorate, potassium bis(fluorosulfonyl)imide, potassium bis(trifluoromethylsulfonyl)imide or potassium hexafluorophosphate, or a combination of at least two thereof; Preferably, the magnesium salt comprises any one or a combination of at least two of magnesium thiocyanate, magnesium perchlorate, magnesium iodide, magnesium bromide, magnesium chloride, magnesium bis(trifluoromethylsulfonyl)imide or magnesium trifluoromethanesulfonate; Preferably, the zinc salt comprises any one or a combination of at least two of zinc thiocyanate, zinc perchlorate, zinc iodide, zinc bromide, magnesium chloride, zinc trifluoromethanesulfonate or bis[bis(trifluoromethylsulfonyl)imide]zinc; Preferably, the aluminum salt includes any one or a combination of at least two of aluminum thiocyanate, aluminum perchlorate, aluminum iodide, aluminum bromide, aluminum chloride or aluminum nitrate; Preferably, the iron salt comprises any one or a combination of at least two of ferric thiocyanate, ferric perchlorate, ferric iodide, ferric bromide, ferric chloride or ferric nitrate; Preferably, the nickel salt includes any one of nickel thiocyanate, nickel perchlorate, nickel iodide or nickel bromide, or a combination of at least two thereof; Preferably, the cobalt salt includes any one or a combination of at least two of cobalt thiocyanate, cobalt perchlorate, cobalt iodide, cobalt bromide or cobalt nitrate; Preferably, the manganese salt comprises any one or a combination of at least two of manganese thiocyanate, manganese perchlorate or manganese nitrate; Preferably, the hydroxyl-containing solvent comprises water and / or an alcohol solvent; Preferably, the alcohol solvent includes any one or a combination of at least two of methanol, ethanol, propanol, isopropanol, butanol, isobutanol, tert-butanol, ethylene glycol, propylene glycol, butanediol, diethylene glycol, triethylene glycol or tetraethylene glycol; Preferably, in the electrolyte gel layer, the molar concentration of the inorganic salt electrolyte is 2.5 mol / L to 12 mol / L, preferably 4.5 mol / L to 9.5 mol / L.
5. The composite solid electrolyte membrane according to any one of claims 1 to 4, characterized in that: The mass ratio of the organic polymer three-dimensional fiber network to the electrolyte gel layer is (0.8-20):1, preferably (3-8):
1.
6. A method for preparing a composite solid electrolyte membrane according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) spraying an organic polymer solution onto a receiving surface by electrospinning to form a polymer three-dimensional fiber web; (2) Mixing an inorganic salt electrolyte solution with a polymer three-dimensional fiber network, and drying the mixture to obtain the composite solid electrolyte membrane.
7. The preparation method according to claim 6, characterized in that: The solvent of the organic polymer solution in step (1) comprises any one of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone or a combination of at least two thereof; Preferably, the concentration of the organic polymer solution in step (1) is 5% to 20%; Preferably, the voltage of the electrospinning in step (1) is 10 kV to 30 kV; Preferably, the liquid flow rate of the electrospinning in step (1) is 5 μL / min to 50 μL / min; Preferably, after the electrospinning treatment in step (1), the obtained polymer three-dimensional fiber web is subjected to a pressing treatment; Preferably, the pressure of the pressing treatment is 10 MPa to 80 MPa.
8. The preparation method according to claim 6 or 7, characterized in that: During the electrospinning in step (1), the inorganic particle dispersion is sprayed onto a receiving surface by electrostatic spraying to mix with the polymer three-dimensional fiber web; Preferably, the solvent of the inorganic particle dispersion includes any one of water, ethanol, isopropanol or N,N-dimethylformamide or a combination of at least two thereof; Preferably, the mass concentration of the inorganic particle dispersion is 2% to 20%; Preferably, the liquid flow rate of the electrostatic spray is 20 μL / min to 80 μL / min; Preferably, the voltage of the electrostatic spray is 10 kV to 30 kV; Preferably, the spraying distances of the electrospinning and electrostatic spraying are independently 3 cm to 25 cm.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The molar concentration of the inorganic salt electrolyte solution in step (2) is 2.5 mol / L to 12 mol / L, preferably 4.5 mol / L to 9.5 mol / L; Preferably, the mixing method in step (2) includes dipping and / or spraying; Preferably, the drying in step (2) comprises vacuum drying; Preferably, the drying temperature in step (2) is 60°C to 80°C.
10. A secondary battery, characterized in that: The secondary battery comprises the composite solid electrolyte membrane according to any one of claims 1 to 5.
Citation Information
Patent Citations
Composite organic solid electrolyte of metal organic framework, and preparation method and application of composite organic solid electrolyte
CN110224174A
Method of improving contact between LLZO solid electrolyte and electrode
CN112563562A
Solid electrolyte's production system
CN208336405U